USM WELCOMES SECOND BATCH OF GAC USA STUDENTS FOR A UNIQUE GUSTAVUS SEMESTER IN MALAYSIA ACADEMIC PROGRAMME - MALAYSIA: LIVING DIVERSITY - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 15 February 2016 Universiti Sains Malaysia (USM) today received and welcomed 10 students from Gustavus Adolphus College (GAC) from Minnesota, United States of America for a semester here under a unique academic programme specially designed together by USM and GAC.